Logística: cadeia de suprimentos dos alimentos - Roncato, Carolina Vieira (2024)
In the contemporary global scenario, efficiency in resource management and food security emerges as crucial challenges. Large scale food production, coupled with population growth, highlights the need to optimize the supply chain and logistics. The loss of food throughout these complex processes is a significant concern. Thus, this study aims to analyze logistics and the supply chain in the food industry through a literature review. The goal was to understand the causes and implications of food loss, provid ing a solid theoretical foundation for efficient and sustainable strategies. A qualitative literature review was conducted through bibliographic research on scientific platforms, including SCIELO, to explore key concepts related to logistics, supply chain, and food loss. The results highlight the main causes of losses along the supply chain, focusing on efficient and sustainable strategies proposed by various authors. The literature review provides an in depth understanding of the interconnection between lo gistics, the supply chain, and food loss. Emphasis is placed on the need for collaborative strategies, the adoption of advanced technologies, and the implementation of sustainable practices to mitigate losses. The study contributes to knowledge about the development of a more efficient, sustainable, and resilient food supply chain, aligned with the principles of social and environmental responsibility.